2016
DOI: 10.3847/0004-637x/828/1/63
|View full text |Cite
|
Sign up to set email alerts
|

Critical Differences of Asymmetric Magnetic Reconnection From Standard Models

Abstract: We have clarified the structure of asymmetric magnetic reconnection in detail as the result of the spontaneous evolutionary process. The asymmetry is imposed as ratio k of the magnetic field strength in both sides of the initial current sheet (CS) in the isothermal equilibrium. The MHD simulation is carried out by the HLLD code for the long-term temporal evolution with very high spatial resolution. The resultant structure is drastically different from the symmetric case (e.g., the Petschek model) even for slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…Our previous studies on the self-similar MRX model (Nitta 2004(Nitta , 2006(Nitta , 2007Nitta et al 2001Nitta et al , 2002Nitta et al , 2016Nitta & Kondoh 2019, 2021 demonstrated slower MRX cases than the Petschek model (higher magnetic Reynolds number cases (Figure 4 of Nitta 2007), thermodynamically asymmetric cases about the CS (Figure 8 of Nitta & Kondoh 2019), and sheared magnetic field cases (Figures 10 and 11 of Nitta & Kondoh 2021)). In these cases, the reconnection rate significantly decreases from a maximum value (prediction of the Petschek model).…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…Our previous studies on the self-similar MRX model (Nitta 2004(Nitta , 2006(Nitta , 2007Nitta et al 2001Nitta et al , 2002Nitta et al , 2016Nitta & Kondoh 2019, 2021 demonstrated slower MRX cases than the Petschek model (higher magnetic Reynolds number cases (Figure 4 of Nitta 2007), thermodynamically asymmetric cases about the CS (Figure 8 of Nitta & Kondoh 2019), and sheared magnetic field cases (Figures 10 and 11 of Nitta & Kondoh 2021)). In these cases, the reconnection rate significantly decreases from a maximum value (prediction of the Petschek model).…”
Section: Introductionmentioning
confidence: 85%
“…The prior works paid scant attention to this point. By considering the consistency across the entire region, the reconnection system can determine itself spontaneously" (Nitta et al 2016).…”
Section: Basic Concept and Numerical Setupmentioning
confidence: 99%
See 3 more Smart Citations